STUDYING THE EFFECT OF BENZOPHENONE ON THERMAL DEGRADATION OF CELLULOSE DIACETATE - Mohamed, Hammed Hashem (Al-Nahrain Journal of Science, 2010)
The induced thermal degradation of cellulose diacetate (CDA) was investigated in the absenceand presence of benzophenone (BPH).CDA are prepared in the laboratory from filter paper, which is characterizated byspectrophotometry (infrared and ultraviolet visible) techniques in addition to the determination ofthe degree of substitution.The addition of (0.5 wt %) of benzophenone to cellulose diacetate enhanced the thermaldegradation of the polymer.Themal degradation rate was measured by ultraviolet visible spectra, decreasing in viscosity andreduction of molecular weight were also observed in the degraded samples. Changes in the numberaveragechain scission and the degree of deterioration. Which were evaluated by analyticaltechniques indicated that the benzophenone enhance the thermal degradation of cellulose diacetate